Development of Higher Order Thinking Skills Based Assessment Instruments Using Live Worksheet Application - Puspitasari, Ratih Octaviana; Wulandari, Siti Sri (Fakultas Ekonomi, Universitas Negeri Semarang, 2021)
The research aimed to develop higher-order thinking skill (HOTS) based assessment instruments based on Live Worksheet applications on Creative Products and Entrepreneurship (PKWU) subjects, especially on Basic Competencies 3.2 Analyzing business opportunities and Basic Competencies 3.3 Applying business administration documents. This research used Sugiyono's development model with seven development steps. The research subject consisted of 34 students of class XI Department of Office Governance Automation SMKS Ketintang Surabaya. The development of this assessment instrument resulted in 20 questions that were declared valid with the calculation of r calculated r table (0.3291). The instrument developed was said to be reliable because the reliability value of the problem of 0.840 0.60 The results of product validation development from three expert validators obtained an average validation of 95.6% with